An auto-tuning modified Smith predictor for delay dominated integrating processes - Somak Karan , Chanchal Dey (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Industrial chemical reactors are usually found to be integrating in nature with significant amount of time delay. To achieve and maintain the desired output from such delay dominated integrating processes is truly a challenging task for process engineers. Here, we propose an auto-tuning scheme for modified Smith predictor based PID controller so that an overall improved process response can be ensured during their close-loop operation. Initial PID tuning parameters are realized using well accepted Ziegler-Nichols ultimate cycle relation. Intricacies due to large dead time is taken care by the well-known modified Smith predictor while the proposed auto-tuning feature will provide improved responses during set point tracking as well as load recovery phases. Performance enhancement of the proposed auto-tuning modified Smith predictor is verified with well-known integrating process models with large dead time representing the behavior of chemical reactors. Considerable improvement is found during simulation study with substantial robustness.